Transformation of Carbon Dioxide into Oxazolidinones and Cyclic Carbonates Catalyzed by Rare‐Earth‐Metal Phenolates. Issue 15 (22nd June 2016) - Xu, Bin; Wang, Peng; Lv, Min; Yuan, Dan; Yao, Yingming
Abstract: Rare‐earth‐metal complexes stabilized by amine‐bridged tri(phenolato) ligands were developed, and their activities in catalyzing transformations of CO2 were studied. A series of terminal epoxides and challenging disubstituted epoxides were converted into the respective cyclic carbonates in the presence of CO2 in yields of 58 to 96 %. In addition, these rare‐earth‐metal complexes also showed good activities in catalyzing three‐component reactions of anilines, epoxides, and CO2, which generated 5‐substituted‐3‐aryl‐2‐oxazolidines in yields of 48 to 96 %, as a useful strategy to construct oxazolidinones. Abstract : A rare find : Rare‐earth‐metal complexes stabilized by amine‐bridged tri(phenolato) ligands are active in catalyzing transformations of CO2 . A series of terminal and disubstituted epoxides are converted into cyclic carbonates in yields of 58 to 96 %. In addition, these rare‐earth‐metal complexes show good activities in catalyzing the three‐component reaction of anilines, epoxides, and CO2, which provides a useful strategy to prepare oxazolidinones.